A New Solution for the Compression of a Two-Layer Strip and Its Application to Analysis of Bonding by Rolling - Sergei Alexandrov; Yusof Mustafa (Advances in Materials Science and Engineering)
The paper presents a theoretical study on the compression of a two-layer strip of strain-hardening rigid-plastic materials between rigid platens. Semianalytical solutions are obtained for stress and velocity fields in each layer. Special attention is devoted to the conditions corresponding to the beginning of cold bond formation between the layers. Depending on input parameters various general deformation patterns are possible. In particular, there exists such a range of process parameters that the soft metal layer yields while the hard metal layer is rigid at the beginning of the process. As the deformation proceeds, yielding also starts in the hard metal layer and the entire strip becomes plastic. This is a typical deformation pattern adopted in describing the process of joining by rolling. However, at a certain range of input parameters plastic deformation of the entire strip begins at the initial instant. Moreover, it is possible that only the hard metal layer yields while the soft metal layer does not. This deformation pattern takes place when the thickness of the soft metal layer is much smaller than that of the hard metal layer.